Agricultural waste assessment for the optimal power generation in the Ludhiana district, Punjab, India. (2022) - Kaur Channi, Harpreet; Singh, Manjeet; Singh Brar, Yadwinder; Dhingra, Arvind; Gupta, Surbhi; Singh, Harpuneet; Kumar, Raman; Kaur, Swapandeep
Abstract: Punjab is a state with enormous biomass potential resource available as crop residue called agri-waste. In the wake of utilizing agricultural waste as local fuel, feeding and thatching, it is widely available. The burning of agricultural-waste in the atmosphere pollutes the environment and promotes global warming. Thereby it is essential to use this waste for human's worthiness. This article presents the region-wise production from biomass build-ups and the surplus potential. Roughly 64 Mty -1 of the total build-up is created from diverse main and insignificant yields, out of which 60.22% is expended in diverse structures, bringing about 40.3% as a net surplus accessible for energy generation. Essential and net surplus product build-ups for energy potential were calculated in every province. Moga, Patiala, Gurdaspur, Ludhiana, and Jalandhar are the actual excess biomass potential areas. In contrast, Pathankot, Fatehgarh Sahib, Rupnagar Shaheed Bhagat Singh Nagar, Bathinda are the least biomass potential locale inside the state. About 1.263 GW and 1.199 GW of energy in the state can be produced using essential and net surplus biomass surplus individually. This paper also discussed the block-wise biomass potential in district Ludhiana. The proposed power plant location in this district, fuel cost, fuel availability and transportation cost are considered as constraints. It has been seen that maximum fuel is available at Sidhwanbet village. Still, by adding transportation cost and comparing results, it has been seen that the effective cost of fuel of plant located at the block–II Ludhiana is minimum.